UNIVERSITIES AS BEACONS OF HOPE IN AN ERA OF CHANGE (Теория и Практика Искусственного Интеллекта: Эксперименты, Проблемы и Перспективы, 2024)
In today's world, where we are surrounded by unprecedented challenges and breathtaking opportunities, the role of universities in shaping the trajectory of societal progress becomes increasingly crucial. Just as the Renaissance marked a period of profound transformation in European society, characterized by a resurgence of learning, creativity, and innovation, we stand today on the cusp of what some envision as a "third renaissance." This essay explores the pivotal role that universities play in laying the groundwork for such a renaissance, examining their contributions to fostering innovation, nurturing critical thinking, promoting interdisciplinary collaboration, and driving societal advancement.